Eco‐Friendly Colloidal Quantum Dot‐Based Luminescent Solar Concentrators - You, Yimin (Adv Sci (Weinh), 2019)
Luminescent solar concentrators (LSCs) have attracted significant attention as promising solar energy conversion devices for building integrated photovoltaic (PV) systems due to their simple architecture and cost‐effective fabrication. Conventional LSCs are generally comprised of an optical waveguide slab with embedded emissive species and coupled PV cells. Colloidal semiconductor quantum dots (QDs) have been demonstrated as efficient emissive species for high‐performance LSCs because of their outstanding optical properties including tunable absorption and emission spectra covering the ultraviolet/visible to near‐infrared region, high photoluminescence quantum yield, large absorption cross sections, and considerable photostability. However, current commonly used QDs for high‐performance LSCs consist of highly toxic heavy metals (i.e., cadmium and lead), which are fatal to human health and the environment. In this regard, it is highly desired that heavy metal‐free and environmentally friendly QD‐based LSCs are comprehensively studied. Here, notable advances and developments of LSCs based on unary, binary, and ternary eco‐friendly QDs are presented. The synthetic approaches, optical properties of these eco‐friendly QDs, and consequent device performance of QD‐based LSCs are discussed in detail. A brief outlook pointing out the existing challenges and prospective developments of eco‐friendly QD‐based LSCs is provided, offering guidelines for future device optimizations and commercialization.